2004
DOI: 10.1002/macp.200400053
|View full text |Cite
|
Sign up to set email alerts
|

Isobutene Polymerization and Copolymerization with Isoprene Initiated by [Cp*TiMe2]+ in the Presence of a Novel Type of Weakly Coordinating Counteranion

Abstract: Summary: The highly electrophilic borane B(C6F5)3 reacts with octadecanoic acid (n‐C17H35CO2H, stearic acid) to form 1:1 and 2:1 adducts [n‐C17H35CO2H][B(C6F5)3] and [n‐C17H35CO2H][B(C6F5)3]2. These adducts exhibit enhanced acidities, and react with Cp*TiMe3 in methylene chloride and toluene to give methane and the complexes [Cp*TiMe2][n‐C17H35CO2{B(C6F5)3}1,2]; the 2:1 complex in particular is a very good initiator for the carbocationic polymerization of isobutene (IB) and copolymerization of IB with isoprene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
(3 reference statements)
3
11
0
Order By: Relevance
“…On the other hand, IB conversions were consistently high in the more polar solvent mix, methyl chloride−methylene chloride. Similar results have been obtained in IB−IP copolymerizations. , …”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…On the other hand, IB conversions were consistently high in the more polar solvent mix, methyl chloride−methylene chloride. Similar results have been obtained in IB−IP copolymerizations. , …”
Section: Resultssupporting
confidence: 88%
“…Given our earlier success using the 2:1 adduct of the borane, B(C 6 F 5 ) 3 , with the long chain n -octadecanoic acid, , we utilized in this study the same 2:1 adduct, [ n -C 17 H 35 CO 2 H][B(C 6 F 5 ) 3 ] 2 , used previously ( D of Scheme ). This behaves as an excellent protic initiator for IB polymerization and IB−IP copolymerization, and as shown in Table , it also behaves as an excellent initiator for IB−DMBD copolymerization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is well known that the rate of chain transfer are strongly affected by the basicity of counteranion and can be minimized using anions that are very weakly nucleophilic 10, 11. Some increase in the monomer conversion and molecular weight can be achieved by modification of B(C 6 F 5 ) 3 by alcohols or carboxylic acids to obtain new weakly coordinating counteranions 12, 13. Further investigations showed that B(C 6 F 5 ) 3 , its derivatives,9, 14–17 or chelating diborane 1,2‐C 6 F 4 [B(C 6 F 5 ) 2 ] 2 18 can be very effective coinitiators for the isobutylene (co)polymerization, if the appropriate initiator was selected thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, all aforementioned systems, especially those based on metallocene initiators, are very sensitive to moisture. Most of the time, polymerizations should be carried out under strictly anhydrous conditions3–9, 12–19 although few studies have shown that the presence of traces of water in the system had in some instances positive effect 6, 9. However, in the late 1990s Sawamoto's team,20 followed by Ganachaud and coworkers,21 showed that rare earth triflates, dodecylbenzenesulfonic acid alone or with Yb(OTf) 3 can induce cationic polymerization of p ‐alkoxystyrenes in aqueous suspension.…”
Section: Introductionmentioning
confidence: 99%